Some factors affecting sclerotium formation in Sclerotium rolfsii - U.P. SINGH, B. PRITHIVIRAJ and (Indian Phytopathology, 2002)
Factors affecting sclerotium formation in S. rolfsii [Corticium rolfsii] were studied. Silica particles of various sizes, colonies of Aspergillus niger and Penicillium species and their culture filtrates formed the basis of experiments. Max. sclerotia formation was observed on/around 250 mesh silica particles. Four times more sclerotia were formed on A. niger colonies while no sclerotia were formed in/on Penicillium spp. colonies. Culture filtrates from either fungi did not affect sclerotium formation.